Slovak Literary Journal Elán (1930 – 1947): : A Case Study in Translation Microhistory - Laš, Matej (chronotopos – A Journal of Translation History, 2022)
The goal of this paper is to analyze the Slovak literary journal Elán edited by poet Ján Smrek from two points of view - translation microhistory (1) focusing on the agency of the translators, which are in this case, also editors of the journal and (2) stressing the translation issues widely discussed in the journal. The journal was formed in 1930 and it was cancelled in 1947 by the leading Communist party. The aim is to quantitively and qualitatively analyze possible shifts in translation policy and in metatranslation discussions in the Slovak part of the First Czechoslovakia, in the Slovak State and during the short period before the communist coup d’état in 1948. The analysis can also show us the first systemic steps in translation within Czechoslovakia and the role of translation in that period. Ján Smrek several times explicitly proclaimed the openness of Slovak culture to foreign influences, therefore his agency in regard to changing ideologies will be analysed.